PENGARUH PENERAPAN SIA, BUDAYA ORGANISASI, KESESUAIAN TUGAS DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BAGIAN AKUNTANSI (STUDI EMPIRIS PADA PERUSAHAAN BUMN DI KOTA BENGKULU) - Elsa Purnama Sari; isma Coryanata (JURNAL FAIRNESS, 2022)
This study aims to examine the effect of applying accounting information systems, organizational culture, suitability of task-technology and work motivation on the performance of accounting department employees at BUMN in Bengkulu City. The data used in this study are primary data. Primary data were obtained from a questionnaire distributed to employees of the accounting department at the BUMN in Bengkulu City. The number of questionnaires distributed was 38 questionnaires, but only 36 questionnaires could be processed. Data were analyzed using multiple linear regression analysis using the SPSS program. The results showed that the application of the accounting information system, organizational culture, task- technology suitability and work motivation had a positive effect on the performance of the accounting department employees at BUMN in Bengkulu City. This research can contribute to SOEs in the city of Bengkulu to be taken into consideration in order to continue to improve the performance of employees in accounting in every company. As for the limitations of this study, this study cannot reach all BUMNs in Bengkulu City because there are a number of BUMN companies that are not willing to be used as research samples.